2011
DOI: 10.1073/pnas.1018519108
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal reorganization in the early deaf switches sensory, but not behavioral roles of auditory cortex

Abstract: It is well known that early disruption of sensory input from one modality can induce crossmodal reorganization of a deprived cortical area, resulting in compensatory abilities in the remaining senses. Compensatory effects, however, occur in selected cortical regions and it is not known whether such compensatory phenomena have any relation to the original function of the reorganized area. In the cortex of hearing cats, the auditory field of the anterior ectosylvian sulcus (FAES) is largely responsive to acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
97
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 45 publications
11
97
0
1
Order By: Relevance
“…In deaf cats, cross-modal activations are spatially specific: They are found in high-level auditory areas and usually do not extend to the primary auditory cortex (20,21,37). To test directly if this specificity is shown in our data, we applied anatomically guided region-of-interest (ROI) analysis of the highlevel auditory cortex (area Te 3) and the primary auditory cortex (the combined areas Te 1.0, Te 1.1, and Te 1.2) (Methods, fMRI Data Analysis) (34,35,38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In deaf cats, cross-modal activations are spatially specific: They are found in high-level auditory areas and usually do not extend to the primary auditory cortex (20,21,37). To test directly if this specificity is shown in our data, we applied anatomically guided region-of-interest (ROI) analysis of the highlevel auditory cortex (area Te 3) and the primary auditory cortex (the combined areas Te 1.0, Te 1.1, and Te 1.2) (Methods, fMRI Data Analysis) (34,35,38).…”
Section: Resultsmentioning
confidence: 99%
“…Several areas in the auditory cortex are known to be recruited for visual and tactile input in the deaf (18)(19)(20)(21)(22). However, the only clear case of task-specific reorganization of the auditory cortex has been demonstrated in deaf cats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…True, task-specific reorganization of the auditory cortex has been demonstrated in deaf cats. Impressive experiments, some of them involving reversible inactivation of auditory cortex with cooling loops, have shown that a distinct auditory area supports peripheral visual localization and visual motion detection in deaf cats, and that the same region supports these functions in the auditory modality in hearing cats (11,12). However, human evidence, in contrast, has been relatively scarce (13).…”
mentioning
confidence: 95%
“…Numerous studies have reported auditory-visual crossmodal reorganization in deaf [1][2][3][4][5][6][7][8][9][10][11][12]. Furthermore, changes in auditory-visual connections and cortical responses to visual stimuli such as the neonatal diversion of retinal axons to the auditory thalamus (cross-modal reorganization) results in the development of a primary auditory cortex that resembles visual cortex in its response properties and topography [1].…”
Section: Introductionmentioning
confidence: 99%